(untitled) (Tanzania Medical Journal, 2010)
Background: Poverty is the state of having little or no money and fewor no material possessions. Poverty can be caused by unemployment, low education, deprivation and homelessness Objective: The aim of this study was to assess the relationship between poverty and patient abandonment (PA) in hospitals, and its impact on health care employing Muhimbili National Hospital (MNH) as a prototype and to assess the attitude of health care professionals (HCPs) towards the patient. Methodology: This was a randomized cross-section study involving patients and HCPs at MNH. Nevertheless, the study targeted all patients who were abandoned at MNH and who voluntarily accepted to participate in this study under informed consent and strict confidentiality. A semi-structured interviewer-administered questionnaire was used to obtain information from the HCPs, while personalized interviews with the patient using structured and semistructured questionnaire were conducted. Poverty assessment toolswere possession of resources, level of education, money (income and expenditure per month and year), and accessibility to basic needs.Findings: A total of 84 respondents who were stratified into 27 HCPs and 57 abandoned patients were involved in the research. This is the first study to be conducted in Dar es Salaam with respect to PA in hospital. Results revealed unnecessary overcrowding in wards and overwhelmingly heavy burden of patient care on the HCPs. The study also observed a correlation between poverty and PA, which was to a great extent related to the patient’s level of education. The respondents strongly condemned PA as demonstration of ungodliness and immoral act. Conclusion and recommendation: Poverty and PA can be alleviated by equipping the citizens with an adequate education and appropriate health care services (HCSs). The government should think of re-introducing subsidies on HCSs in order to alleviate the burden of medical expenses incurred by the low income citizens, particularly the unemployed and farmers. The study also recommends that the government should improve HCSs in regional hospitals in order to reduce/avoid travel and general patients careexpenses.Key words: Poverty, patient abandonment, health care services, level of education